2019
DOI: 10.1038/s41467-018-08129-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic ATF6 activation confers global protection in widespread disease models by reprograming cellular proteostasis

Abstract: Pharmacologic activation of stress-responsive signaling pathways provides a promising approach for ameliorating imbalances in proteostasis associated with diverse diseases. However, this approach has not been employed in vivo. Here we show, using a mouse model of myocardial ischemia/reperfusion, that selective pharmacologic activation of the ATF6 arm of the unfolded protein response (UPR) during reperfusion, a typical clinical intervention point after myocardial infarction, transcriptionally reprograms proteos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
150
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 46 publications
6
150
0
1
Order By: Relevance
“…Despite several studies demonstrating the efficacy of ATF6 in mitigating AMI injury, the mechanism of how ATF6, an ER-resident transcription factor, could protect from reperfusion damage associated with AMI or stroke, most of which is caused by oxidative stress and ROS generated by mitochondria, remained elusive. Accordingly, to address this mechanism, recent studies used either a mouse model where ATF6 had been globally deleted (ATF6 KO) [28] or generated a mouse model in which ATF6 is conditionally deleted only in cardiac myocytes (ATF6 cKO) [116]. Transcript profiling of ATF6 transgenic and ATF6 cKO mice revealed that in addition to genes encoding proteins that constitute the ER protein-folding machinery, ATF6 induces genes that encode proteins that do not even reside in the ER.…”
Section: Atf6 Is Protective In Models Of Acute Myocardial Infarctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite several studies demonstrating the efficacy of ATF6 in mitigating AMI injury, the mechanism of how ATF6, an ER-resident transcription factor, could protect from reperfusion damage associated with AMI or stroke, most of which is caused by oxidative stress and ROS generated by mitochondria, remained elusive. Accordingly, to address this mechanism, recent studies used either a mouse model where ATF6 had been globally deleted (ATF6 KO) [28] or generated a mouse model in which ATF6 is conditionally deleted only in cardiac myocytes (ATF6 cKO) [116]. Transcript profiling of ATF6 transgenic and ATF6 cKO mice revealed that in addition to genes encoding proteins that constitute the ER protein-folding machinery, ATF6 induces genes that encode proteins that do not even reside in the ER.…”
Section: Atf6 Is Protective In Models Of Acute Myocardial Infarctionmentioning
confidence: 99%
“…As described throughout this review, maintaining cardiac myocyte proteostasis is vital for cellular viability and function, and ATF6 has demonstrated efficacy as a therapeutic target for CVD and cardiac hypertrophy [27,50,116]. Thus, a conceptual framework with specific research approaches was designed in an attempt to identify key proteostasis regulatory pathways via discovering non-canonical gene targets of ATF6 using diverse animal models of various etiologies contributing to CVD.…”
Section: Small Molecule Atf6-activators Confer Protection Against Carmentioning
confidence: 99%
See 1 more Smart Citation
“…NRCMs were isolated as previously described 21,22 and seeded in a 6-well dish at a density of 10 200,000 per well in M199 media with 15% fetal bovine serum (FBS). The following day, cells 11…”
Section: Cell Death Assay 15mentioning
confidence: 99%
“…ATF6 activation is considered to be the pro-survival branch of the UPR, improving stroke outcomes (53) and myocardial ischemia/reperfusion injury (54,55). In the pancreatic beta cell, ATF6 is needed for beta cell proliferation and compensation during insulin resistance (24) and ATF6-null mice do not display any defects in ÎČ-cell function on a normal chow diet but experience severe ER stress with reduced insulin content during HFD (56).…”
mentioning
confidence: 99%